Scientific Opinion on the safety and efficacy of citric acid when used as a technological additive (acidity regulator) for all animal species. (17th February 2015) - ,; ,
Abstract: An application has been made for the authorisation of citric acid (anhydrous and monohydrate) when used as an acidity regulator in feed and in water for drinking for all animal species. Citric acid (anhydrous and monohydrate) is already authorised for use in food following the quantum satis principle. There is evidence from published studies that citric acid is safe for the target species when used up to 30 000 mg citric acid/kg complete feedingstuffs and the corresponding concentration in water for drinking (10 000 mg citric acid/L). The additive is consequently also safe for the target species at the proposed conditions of use of 15 000 mg citric acid/kg complete feedingstuffs and 5 000 mg citric acid/L in water for drinking. The quality of the available data does not allow a margin of safety to be derived. The use of citric acid in animal nutrition is safe for the consumer. It is prudent to regard citric acid as potentially hazardous to workers by exposure of the skin, eyes or mucous membranes or by inhalation. The use of citric acid in animal nutrition would not pose a risk for the environment. The addition of citric acid reduces the pH of aqueous suspensions of compound feedingstuffs and feed materials. However, the relevance of pH and buffer capacity measurements made with aqueous suspensions to the effects of citric acid in dry feed (< 12 % moisture) is open to question. Citric acid might have the potential to act as an acidity regulator in feedingstuffs.